2022
DOI: 10.3390/cancers14030676
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity Score Matched Analysis of Superparamagnetic Iron Oxide versus Radioisotope Sentinel Node Biopsy in Breast Cancer Patients after Neoadjuvant Chemotherapy

Abstract: The standard method for nodal staging in breast cancer (BC) patients after neoadjuvant chemotherapy (NAC) is sentinel lymph node biopsy (SLNB) with a radioisotope (RI) injection. However, SLNB after NAC results in high false-negative rates (FNR), and the RI method is restricted by nuclear medicine unit dependency. These limitations resulted in the development of the superparamagnetic iron oxide (SPIO) method, reducing FNR and presenting a comparable detection rate. This bi-institutional cohort comparison study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Studies had reported a 100% identification rate of SLNB with SPIO for patients after neoadjuvant chemotherapy. 32 , 33 Besides, compared to the radioisotope, it can significantly improve the median of retrieved sentinel lymph nodes (3 vs. 2, P < .0001), while radioisotope is considered the standard tracer of SLNB in breast cancer patients after neoadjuvant chemotherapy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Studies had reported a 100% identification rate of SLNB with SPIO for patients after neoadjuvant chemotherapy. 32 , 33 Besides, compared to the radioisotope, it can significantly improve the median of retrieved sentinel lymph nodes (3 vs. 2, P < .0001), while radioisotope is considered the standard tracer of SLNB in breast cancer patients after neoadjuvant chemotherapy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…It flows through the lymphatic system and is trapped by the SLN, becoming detectable by a hand-held magnetometer. The SPIO method showed a significantly higher chance versus the radioactive tracer method in both retrieving (71% vs. 11.3%; OR = 19.21; p < 0.0001) and evaluating (71.4% vs. 51.6%; OR = 3.21; p = 0.0032) at least three SLNs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%